Non-aqueous electrolyte solution for lithium secondary battery and lithium secondary battery comprising same

By using non -hydrolytic fluid containing benzene and dual alkane compounds in lithium secondary batteries, the problem of deterioration of battery performance under high voltage/high temperature conditions is solved, and better membrane durability and electrolyte stability are achieved, extending Battery life.

CN119366024APending Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380047307.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2023-07-07
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When the lithium secondary battery operates under high voltage/high temperature conditions, the lithium salt decomposition product in the electrolyte is intensified, resulting in membrane damage, decomposition of electrode active material and dissolution and deposition of transition metal ions, thereby damaging the battery performance.

Method used

A non -hydrolyar electrolyte containing a lithium salt, organic solvent, and a phenyl vulcanotic compounds represented by chemical 1. This compound has unsaturated keys and benzene ring structures. Durability and physical strength, and inhibit the decomposition of electrolytes.

Benefits of technology

The non -hydrolybility can reduce the decomposition response of the electrolyte under high voltage/high temperature conditions, inhibit the dissolving and gas generation of transition metals, extend the life of lithium secondary batteries, and improve its electrochemical characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189245080000021
    Figure BDA0005189245080000021
  • Figure BDA0005189245080000041
    Figure BDA0005189245080000041
  • Figure BDA0005189245080000051
    Figure BDA0005189245080000051
Patent Text Reader

Abstract

The present invention relates to a non-aqueous electrolyte solution for a lithium secondary battery and a lithium secondary battery comprising the same, the non-aqueous electrolyte solution comprising a compound represented by chemical formula 1, a lithium salt, and an organic solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Korean Patent Application No. 10-2022-0085817 filed on Jul. 12, 2022 and Korean Patent Application No. 10-2023-0087775 filed on Jul. 6, 2023, the disclosures of which are incorporated herein by reference.

[0002] The present invention relates to a non-aqueous electrolyte for a lithium secondary battery and a lithium secondary battery containing the non-aqueous electrolyte. Background Art

[0003] A lithium secondary battery is generally prepared by forming an electrode assembly by providing a separator between a positive electrode (comprising a positive electrode active material formed of a lithium-containing transition metal oxide) and a negative electrode (comprising a negative electrode active material capable of storing lithium ions) and inserting the electrode assembly into a battery case, injecting a nonaqueous electrolyte as a medium for transmitting lithium ions therein, and then sealing the battery case.

[0004] Since lithium secondary batteries can be miniaturized and have high energy density and operating voltage, they are being used in various fields such as mobile devices, electronic products, and electric vehicles. As the application fields of lithium secondary batteries diversify, the required physical property conditions are gradually improving. Specifically, it is necessary to develop a lithium secondary battery that can operate stably even under high voltage / high temperature conditions and has long life characteristics.

[0005] When lithium secondary batteries are operated under high voltage / high temperature conditions, lithium salts (such as LiPF 6 ) decomposes PF 6- The reaction of anions may be enhanced to form Lewis acids, such as PF 5 , which reacts with moisture to form HF. 5 The decomposition products such as HF may not only destroy the film formed on the electrode surface, but may also cause a decomposition reaction of the organic solvent, and may react with the decomposition products of the positive electrode active material to dissolve transition metal ions. The dissolved transition metal ions may be electrodeposited on the negative electrode and destroy the film formed on the negative electrode surface.

[0006] If the electrolyte decomposition reaction continues on the damaged membrane, the battery performance will further deteriorate. Therefore, it is necessary to develop a secondary battery that can maintain excellent performance even under high voltage / high temperature conditions. Summary of the invention

[0007] Technical issues

[0008] One aspect of the present invention provides a nonaqueous electrolyte that helps form a reinforced film on an electrode, and a lithium secondary battery including the nonaqueous electrolyte.

[0009] Technical Solution

[0010] According to one embodiment of the present invention, a non-aqueous electrolyte for a lithium secondary battery is provided, which includes: a lithium salt; an organic solvent; and a compound represented by Chemical Formula 1.

[0011] [Chemical formula 1]

[0012]

[0013] In Chemical Formula 1,

[0014] R1 is -COR, -COOR', -NCO, a nitrile group, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms,

[0015] R2 is: a halogen group; -COR"; -COOR"'; -NCO; a nitrile group; an alkyl group having 1 to 10 carbon atoms which is unsubstituted or substituted with at least one halogen group; an alkenyl group having 2 to 10 carbon atoms; or an alkynyl group having 2 to 10 carbon atoms,

[0016] R, R', R", and R'" are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms,

[0017] n is 1 or 2. When n is 2, two R1s are the same as or different from each other, and

[0018] m is any integer from 0 to 8-n.

[0019] According to another aspect of the present invention, a lithium secondary battery is provided, comprising: a positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; a separator disposed between the positive electrode and the negative electrode; and a nonaqueous electrolyte for the lithium secondary battery.

[0020] Beneficial Effects

[0021] The non-aqueous electrolyte solution of the present invention has the effect of forming an ether film by an oxidation reaction at the positive electrode / negative electrode of a lithium secondary battery by containing a benzodioxane compound having a substituent having an unsaturated bond.

[0022] Since ether membranes have better flexibility than carbonate membranes, they can effectively suppress membrane collapse and continuous decomposition of electrolytes in batteries containing silicon (Si) negative electrode active materials with large volume changes. In addition, since benzodioxane compounds contain benzene rings, they react quickly with active oxygen generated by structural changes in positive electrode active materials under high voltage operating conditions, thereby suppressing the oxidation reaction of the electrolyte, and thus, ultimately providing lithium secondary batteries with improved electrochemical characteristics. DETAILED DESCRIPTION

[0023] Hereinafter, the present invention will be described in more detail.

[0024] Generally, lithium salts (such as LiPF 6 ) will form decomposition products due to thermal decomposition or water, such as hydrogen fluoride (HF) and PF 5 These decomposition products are acidic and can degrade the membrane or electrode surface in the battery.

[0025] Due to the decomposition products of the electrolyte and the changes in the positive electrode structure caused by repeated charge and discharge, the transition metal in the positive electrode is easily dissolved into the electrolyte, and the dissolved transition metal will be redeposited on the positive electrode, thereby increasing the resistance of the positive electrode. In addition, when the dissolved transition metal moves to the negative electrode through the electrolyte, the dissolved transition metal will be electrodeposited on the negative electrode, causing the destruction of the solid electrolyte interface (SEI) film and additional electrolyte decomposition reactions, resulting in problems such as lithium ion consumption and increased resistance.

[0026] In addition, during the initial activation of the battery, a protective film may be formed on the positive and negative electrodes by electrolyte reaction, wherein, if the film becomes unstable due to the above reasons, additional decomposition of the electrolyte occurs during charging and discharging or during exposure to high temperatures, thereby promoting battery degradation and generating gas.

[0027] As the demand for high-performance lithium secondary batteries increases, it is necessary to introduce silicon-based negative electrode active materials with theoretical capacity much higher than graphite to improve energy density. However, since silicon-based negative electrode active materials have a very high volume change rate compared to graphite, in order to compensate for this shortcoming, a flexible and highly durable film needs to be formed on the negative electrode.

[0028] The operating voltage required to improve the energy density also increases, wherein there is a problem that the above-mentioned electrolyte decomposition reaction and the resulting degradation of battery performance are further aggravated during operation at a high voltage.

[0029] In order to solve these problems, the present inventors included the compound represented by Chemical Formula 1 in a non-aqueous electrolyte, and found that the decomposition reaction of the electrolyte can be reduced, and the dissolution of transition metals and gas generation can be suppressed.

[0030] Specifically, since the benzodioxane compound represented by the following Chemical Formula 1 contains an organic structure having an unsaturated bond, it can have the effect of improving the durability of the membrane by causing a polymerization reaction with free radicals generated by direct electrolysis or electrolyte decomposition on the electrode surface, and can also form a flexible polymer film containing an ether structure by decomposition of an oxygen-containing ring structure (i.e., dioxane), thereby confirming that a long life can be achieved even in a battery using a silicon-based negative electrode active material with a large volume change.

[0031] In the case where the battery is operated at a high voltage to increase the energy density, there is a problem that the electrolyte decomposition rate increases when active oxygen is scavenged due to the collapse of the cathode structure.

[0032] However, the inventors have confirmed that when a non-aqueous electrolyte contains a compound represented by the following chemical formula 1, since the benzene ring structure contained in the compound can react with active oxygen faster than the electrolyte, the decomposition of the electrolyte can be suppressed and a long life can be achieved even at a high operating voltage of more than 4.25 V, specifically more than 4.3 V.

[0033] Hereinafter, each component constituting the present invention will be described in more detail.

[0034] Non-aqueous electrolyte

[0035] The present invention provides a non-aqueous electrolyte for a lithium secondary battery, which includes: a lithium salt; an organic solvent; and a compound represented by Chemical Formula 1.

[0036] Hereinafter, each component will be described in detail.

[0037] (1) The compound represented by Chemical Formula 1

[0038] The nonaqueous electrolyte of the present invention includes a compound represented by the following Chemical Formula 1.

[0039] [Chemical formula 1]

[0040]

[0041] In Chemical Formula 1,

[0042] R1 is -COR, -COOR', -NCO, a nitrile group, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms,

[0043] R and R' are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms,

[0044] R2 is: a halogen group; or an alkyl group having 1 to 10 carbon atoms which is unsubstituted or substituted with at least one halogen group,

[0045] n is 1 or 2. When n is 2, two R1s are the same as or different from each other, and

[0046] m is any integer from 0 to 8-n.

[0047] The oxygen-containing ring structure in benzodioxane of Chemical Formula 1 can increase the flexibility of the polymer contained in the membrane when decomposed, thereby minimizing the decomposition of the membrane at high temperatures, while the benzene ring structure can increase the physical strength of the membrane while having the effect of inhibiting the decomposition of the electrolyte by reacting with active oxygen.

[0048] However, in the case where the dioxane ring does not contain a substituent or is substituted with a halogen group or oxygen (=O), a product in the form of a gas may be generated due to the decomposition of dioxane, wherein, in the case where the R1 substituent is contained as in the compound of Chemical Formula 1, the durability of the film can be improved by forming a cross-linked polymer while reducing the amount of gas generated. Specifically, the carbon-carbon multiple bonds or carbon-heteroatom multiple bonds of R1 can help increase the density of the film formed on the electrode by polymerization.

[0049] In addition, the benzene ring in benzodioxane of Chemical Formula 1 plays a role in scavenging active oxygen compounds by combining with active oxygen compounds, wherein, since the R1 substituent is substituted on the dioxane ring instead of the benzene ring, it is ideal in that the above effect can be achieved without affecting the active oxygen scavenging effect.

[0050] In one embodiment of the present invention, R1 in Chemical Formula 1 may be -COR, -COOR', -NCO or a nitrile group.

[0051] In addition, R and R' can each independently be an alkyl group having 1 to 10 carbon atoms or an alkynyl group having 2 to 10 carbon atoms, and can be preferably a methyl group or a propargyl group. Preferably, R1 in Chemical Formula 1 is -COR or -COOR', and R and R' can be an alkenyl group having 2 to 10 carbon atoms or an alkynyl group having 2 to 10 carbon atoms. As described above, in the case of replacing -CO- or -COO- with multiple bonds, it is beneficial to form a film containing oxygen, and since the unshared electron pairs of oxygen can improve the hopping of lithium ions, it has the effect of improving ionic conductivity and reducing battery resistance. In addition, in the case of containing carbon-carbon multiple bonds, since it is beneficial to form a cross-linked polymer by decomposition compared with substituents containing carbon-nitrogen multiple bonds (such as -NCO and nitrile groups), the resistance increase rate of the battery can be reduced.

[0052] R1 in Chemical Formula 1 may be -COCH 3 、-COO(CH 2 )CCH, -NCO or nitrile, and more preferably -COO(CH 2 )CCH.

[0053] In another embodiment of the present invention, when R1 in Chemical Formula 1 is a substituent containing a carbon-carbon multiple bond, i.e., -COR, -COOR', an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms, R and R' may each independently be an alkenyl group having 2 to 10 carbon atoms or an alkynyl group having 2 to 10 carbon atoms.

[0054] In one embodiment of the present invention, the compound represented by Chemical Formula 1 may be represented by the following Chemical Formula 1-1.

[0055] [Chemical formula 1-1]

[0056]

[0057] In Chemical Formula 1-1,

[0058] R1 and R2 are as defined in Formula 1, and

[0059] k is an integer from 0 to 4.

[0060] In one embodiment of the present invention, R2 may be: the same substituent as R1, fluorine; or an alkyl group having 1 to 10 carbon atoms substituted with at least one fluorine, and k may be 0 or 1. As described above, in the case where R2 is substituted on the benzene ring, it is preferred in that the durability of the thin film can be improved as the density of the film formed on the electrode increases.

[0061] In one embodiment of the present invention, Chemical Formula 1 may be represented by any one of the following Chemical Formulas 1A to 1D, and may be preferably represented by Chemical Formula 1A. Since the structure of Chemical Formula 1A includes carbon-carbon multiple bonds, it is preferred in terms of improving the durability of the film on the electrode as described above.

[0062] [Chemical Formula 1A]

[0063]

[0064] [Chemical formula 1B]

[0065]

[0066] [Chemical formula 1C]

[0067]

[0068] [Chemical formula 1D]

[0069]

[0070] In terms of sufficiently achieving the above-mentioned addition effect, the amount of the compound represented by Chemical Formula 1 may be 0.1 wt % or more, preferably 0.15 wt % or more, and more preferably 0.2 wt % or more, based on the total weight of the nonaqueous electrolyte.

[0071] However, in terms of preventing rapid increase in resistance due to excessive film formation, the amount of the compound represented by Chemical Formula 1 may be 5 wt % or less, preferably 3 wt % or less, and more preferably 1 wt % or less, based on the total weight of the nonaqueous electrolyte.

[0072] Most preferably, the amount of the compound represented by Chemical Formula 1 may be 0.2 wt % or more and 0.5 wt % or less.

[0073] (2) Additives

[0074] In order to prevent the electrolyte from decomposing under high voltage environment and causing electrode collapse, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge protection and battery expansion inhibition effect at high temperature, the non-aqueous electrolyte of the present invention may optionally contain the following additives if necessary.

[0075] The additive may be at least one selected from the group consisting of cyclic carbonate compounds, sultone compounds, sulfate compounds, phosphorus compounds, nitrile compounds, amine compounds, silane compounds, benzene compounds, and lithium salt compounds.

[0076] The cyclic carbonate compound may be at least one selected from the group consisting of vinylene carbonate (VC), vinyl ethylene carbonate (VEC) and fluoroethylene carbonate (FEC), and specifically may be vinylene carbonate.

[0077] The sultone compound is a material that can form a stable SEI film on the surface of the negative electrode through a reduction reaction, wherein the sultone compound can be at least one selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethane sultone, prop-1-ene-1,3-sultone (PRS), 1,4-butene sultone and 1-methyl-1,3-propene sultone, specifically 1,3-propane sultone (PS) or prop-1-ene-1,3-sultone (PRS).

[0078] Sulfate ester compounds are materials that can be electrolyzed on the surface of the negative electrode to form a stable SEI film that will not crack even during high-temperature storage, wherein the sulfate ester compound can be at least one selected from the group consisting of ethylene sulfate (Esa), trimethylene sulfate (TMS) and methyl trimethylene sulfate (MTMS).

[0079] The phosphorus compound may be a phosphate compound or a phosphite compound, specifically, at least one selected from the group consisting of tris(trimethylsilyl) phosphate, tris(trimethylsilyl) phosphite, tris(2,2,2-trifluoroethyl) phosphate and tris(trifluoroethyl) phosphite.

[0080] The nitrile compound may be at least one selected from the group consisting of succinonitrile (SN), adiponitrile (ADN), acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanenitrile, cyclopentanenitrile, cyclohexanenitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorophenyl acetonitrile, 4-fluorophenyl acetonitrile, ethylene glycol di(2-cyanoethyl) ether (ASA3), 1,3,6-hexanetrinitrile (HTCN), 1,4-dicyano-2-butene (DCB) and 1,2,3-tris(2-cyanoethyl)propane (TCEP).

[0081] The amine compound may be at least one selected from the group consisting of triethanolamine and ethylenediamine, and the silane compound may be tetravinylsilane.

[0082] The benzene compound may be at least one selected from the group consisting of monofluorobenzene, difluorobenzene, trifluorobenzene, and tetrafluorobenzene.

[0083] The lithium salt compound is a compound different from the lithium salt contained in the non-aqueous electrolyte, wherein the lithium salt compound can be selected from lithium difluorophosphate (LiDFP; LiPO 2 F 2), lithium bis(oxalatoborate) (LiBOB; LiB(C 2 O 4 ) 2 ), lithium tetrafluoroborate (LiBF 4 ), at least one of the group consisting of lithium tetraphenylborate, lithium difluorooxalatoborate (LiDFOB) or lithium difluorobisoxalatophosphate (LiDFOP).

[0084] Preferably, the non-aqueous electrolyte of one embodiment of the present invention may further include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), succinonitrile (SN), 1,3,6-hexanetrinitrile (HTCN), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4 ), 1,3-propane sultone (PS), prop-1-ene-1,3-sultone (PRS), ethylene sulfate (Esa) and lithium difluorophosphate (LiDFP) The group consisting of at least one additive may more preferably include fluoroethylene carbonate. In this case, since the additive can form a film on the positive electrode and the negative electrode together with the compound represented by Chemical Formula 1 to improve the film durability and reduce the resistance at the same time, the battery performance can be improved.

[0085] The content of the additive may be 0.1 wt % to 10 wt %, preferably 0.2 wt % to 5 wt %, based on the total weight of the non-aqueous electrolyte. When the content of the additive is within the above range, it has the effect of suppressing side reactions by forming a film on the positive electrode and the negative electrode.

[0086] (3) Organic solvents

[0087] The nonaqueous electrolyte solution of the present invention contains an organic solvent.

[0088] Various organic solvents commonly used in lithium electrolytes can be used as organic solvents without limitation. For example, the organic solvent can be a cyclic carbonate solvent, a linear carbonate solvent, a linear ester solvent, a cyclic ester solvent, a nitrile solvent or a mixture thereof, preferably can include a mixture of at least two selected from the group consisting of a cyclic carbonate solvent, a linear carbonate solvent and a linear ester solvent, and can more preferably include a mixture of a cyclic carbonate solvent and a linear carbonate solvent.

[0089] The cyclic carbonate solvent can dissociate the lithium salt in the electrolyte well due to its high dielectric constant as a high-viscosity organic solvent, wherein the cyclic carbonate solvent can be at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate and vinylene carbonate, preferably including ethylene carbonate (EC) or propylene carbonate (PC).

[0090] In addition, the linear carbonate solvent is an organic solvent with low viscosity and low dielectric constant, wherein the linear carbonate solvent can be at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, and can preferably include ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or diethyl carbonate (DEC).

[0091] In order to prepare an electrolyte having high ion conductivity, it is desirable to use a mixture of a cyclic carbonate-based solvent and a linear carbonate-based solvent as the organic solvent.

[0092] The linear ester solvent may be at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate and butyl propionate, and may preferably be methyl propionate, ethyl propionate or propyl propionate.

[0093] The cyclic ester-based solvent may be at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.

[0094] In addition, the nitrile solvent can be at least one selected from the group consisting of succinonitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanenitrile, cyclopentanenitrile, cyclohexanenitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorophenyl cyanide and 4-fluorophenyl cyanide, and can preferably be succinonitrile.

[0095] Unless otherwise specified, the rest of the components other than the organic solvent in the total weight of the non-aqueous electrolyte (eg, the amount of the compound represented by Chemical Formula 1, additives, and lithium salt) may all be organic solvents.

[0096] (4) Lithium salt

[0097] The nonaqueous electrolyte of the present invention contains a lithium salt.

[0098] Any lithium salt commonly used in non-aqueous electrolytes for lithium secondary batteries may be used as the lithium salt without limitation. Specifically, the lithium salt may include Li +as a cation, and may contain at least one selected from the group consisting of: F - , Cl - Br - ,I - 、NO 3 - 、N(CN) 2 - , BF 4 - , ClO 4 - , B 10 Cl 10 - 、AlCl 4 - 、AlO 2 - PF 6 - CF 3 SO 3 - , CH 3 CO 2 - CF 3 CO 2 - , AsF 6 - , SbF 6 - , CH 3 SO 3 - ,(CF 3 CF 2 SO 2 ) 2 N - ,(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - , BF 2 C 2 O 4 - , B.C. 4 O 8 - , BF 2 C 2 O 4 CHF-、PF 4 C 2 O 4 - PF 2 C 4 O8 - ,PO 2 F 2 - ,(CF 3 ) 2 PF 4 - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - , C 4 F 9 SO 3 - CF 3 CF 2 SO 3 - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - CF 3 (CF 2 ) 7 SO 3 - and SCN - .

[0099] Specifically, the lithium salt may be selected from LiPF 6 、LiClO 4 , LiBF 4 、Lithium bis(fluorosulfonyl)imide (LiN(FSO 2 ) 2 ; LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI), lithium trifluoromethanesulfonate (LiSO 3 CF 3 ), lithium difluorophosphate (LiPO 2 F 2At least one of the group consisting of lithium bis(oxalato)borate (LiBOB), lithium difluorooxalatoborate (LiFOB), lithium difluorobis(oxalato)phosphate (LiDFOP), lithium tetrafluorooxalatophosphate (LiTFOP) and lithium difluoroborate fluoromalonate (LiFMDFB), preferably LiPF 6 .

[0100] In one embodiment of the present invention, the concentration of the lithium salt in the non-aqueous organic solution containing the lithium salt and the organic solvent may be 0.5 M to 4.0 M, specifically 0.5 M to 3.0 M, and more specifically 0.8 M to 2.0 M. When the lithium salt concentration is within the above range, sufficient electrolyte impregnation can be obtained by preventing excessive increases in viscosity and surface tension while sufficiently ensuring the effects of improving low-temperature output and improving cycle characteristics.

[0101] Lithium secondary battery

[0102] Next, the lithium secondary battery of the present invention will be described.

[0103] The lithium secondary battery of the present invention comprises a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte. In this case, the non-aqueous electrolyte is the non-aqueous electrolyte of the present invention described above. Since the non-aqueous electrolyte has been described above, its description will be omitted, and other components will be described below.

[0104] (1) Positive electrode

[0105] The positive electrode of the present invention includes a positive electrode active material, and can be prepared by coating a positive electrode collector with a positive electrode slurry containing the positive electrode active material, a binder, a conductive agent, and a solvent, and then drying and rolling the coated positive electrode collector.

[0106] There is no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, stainless steel; aluminum; nickel; titanium; fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium or silver can be used.

[0107] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium, wherein the positive electrode active material may be at least one selected from the group consisting of: LCO (LiCoO 2 ); LNO(LiNiO 2 ); LMO(LiMnO 2 ); LiMn 2 O 4 ;LiCoPO 4 ;LFP(LiFePO 4); and a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co) and manganese (Mn).

[0108] The molar ratio of nickel in the transition metal of the positive electrode active material may be 60 mol % or more, preferably 70 mol % or more, and more preferably 80 mol % or more.

[0109] In one embodiment of the present invention, the lithium composite transition metal oxide may be a compound represented by the following Chemical Formula 2. That is, the positive electrode active material in one embodiment of the present invention may include the lithium composite transition metal oxide represented by the following Chemical Formula 2.

[0110] [Chemical formula 2]

[0111] Li 1+x (Ni a Co b Mn c M d ) 2

[0112] In chemical formula 2,

[0113] M is at least one selected from the group consisting of tungsten (W), copper (Cu), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), zirconium (Zr), zinc (Zn), aluminum (Al), indium (In), tantalum (Ta), yttrium (Y), lanthanum (La), strontium (Sr), gallium (Ga), scandium (Sc), gadolinium (Gd), samarium (Sm), calcium (Ca), cerium (Ce), niobium (Nb), magnesium (Mg), boron (B) and molybdenum (Mo), and

[0114] 1+x, a, b, c and d are the atomic fractions of the individual elements,

[0115] Among them, -0.2≤x≤0.2, 0.6≤a<1, 0 <b≤0.3,0<c≤0.3,0≤d≤0.1,a+b+c+d=1。

[0116] 1+x represents the molar ratio of lithium in the lithium composite transition metal oxide, wherein x may satisfy -0.1≤x≤0.2 or 0≤x≤0.2. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium composite transition metal oxide may be stably formed.

[0117] a represents the molar ratio of nickel in all metals other than lithium in the lithium composite transition metal oxide, wherein a may satisfy 0.70≤a<1, 0.75≤a<1, or 0.80≤a<1. When the molar ratio of nickel satisfies the above range, high energy density may be exhibited, thereby achieving high capacity.

[0118] b represents the molar ratio of cobalt in all metals other than lithium in the lithium composite transition metal oxide, where b can satisfy 0 < b ≤ 0.20, 0 < b ≤ 0.18, or 0 < b ≤ 0.15. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be achieved.

[0119] c represents the molar ratio of manganese in all metals other than lithium in the lithium composite transition metal oxide, where c can satisfy 0 < c ≤ 0.20, 0 < c ≤ 0.18, or 0 < c ≤ 0.15. When the molar ratio of manganese satisfies the above range, the structural stability of the positive electrode active material is excellent.

[0120] In one embodiment of the present invention, the lithium composite transition metal oxide may include at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo. In other words, d represents the molar ratio of the doping element in all metals other than lithium in the lithium composite transition metal oxide, and d can satisfy 0 < d ≤ 0.10, 0 < d ≤ 0.08, or 0 < d ≤ 0.05.

[0121] Preferably, a, b, c, and d in Chemical Formula 2 can respectively satisfy 0.70 ≤ a < 1, 0 < b ≤ 0.2, 0 < c ≤ 0.2, and 0 ≤ d ≤ 0.1.

[0122] In another embodiment of the present invention, the lithium composite transition metal oxide may be at least one selected from the group consisting of: Li p Mn 1-q M q A 2 、Li p Mn 2 O 4-r X r 、Li p Mn 2-q M q M’ r A 4 、Li p Co 1-q M q A 2 、Li p Co 1-q M q O 2-r X r 、Li p Ni 1-q M q O 2-r X r 、Li p Ni 1-qCo q O 2-r X r , Li p Ni 1-q-r Co q M r A w , Li p Ni 1-q-r Co q M r O 2-w X w , Li p Ni 1-q-r Mn q M r A w and Li p Ni 1-q-r Mn q M r O 2-w X w , wherein p, q, r and w satisfy 0.9≤p≤1.2, 0≤q≤1, 0≤r≤1 and 0≤w≤2 respectively, M and M' are the same as or different from each other and are one or more elements selected from the group consisting of Mg, Al, Co, potassium (K), sodium (Na), Ca, silicon (Si), Ti, tin (Sn), V, germanium (Ge), Ga, B, arsenic (As), Zr, Mn, Cr, Fe, Sr, V and rare earth elements, A is at least one element selected from the group consisting of oxygen (O), fluorine (F), sulfur (S) and phosphorus (P), and X is at least one element selected from the group consisting of F, S and P.

[0123] Based on the total weight of the solids in the positive electrode slurry, the content of the positive electrode active material may be 80 wt % to 99 wt %, specifically 90 wt % to 99 wt %. When the content of the positive electrode active material is less than 80 wt %, the capacity may be reduced due to the reduced energy density.

[0124] The binder is a component that helps the bonding between the active material and the conductive agent and the bonding with the current collector, wherein the binder is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solids in the positive electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0125] In addition, the conductive agent is a material that can provide conductivity without causing adverse chemical changes in the battery, wherein the added amount thereof may be 0.5 wt % to 20 wt % based on the total weight of the solids in the positive electrode slurry.

[0126] For example, the conductive agent can be selected from conductive materials such as: carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; graphite powder, such as natural graphite, artificial graphite, carbon nanotubes and graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as fluorinated carbon powder, aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives.

[0127] In addition, the solvent of the positive electrode slurry may include: an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that a desired viscosity is obtained when the positive electrode active material, the binder and the conductive agent are included. For example, the content of the solvent may be such that the concentration of the solids in the positive electrode slurry containing the positive electrode active material, the binder and the conductive agent is 40 wt % to 90 wt %, preferably 50 wt % to 80 wt %.

[0128] (2) Negative electrode

[0129] The negative electrode of the present invention includes a negative electrode active material, and can be prepared by coating a negative electrode collector with a negative electrode slurry containing the negative electrode active material, a binder, a conductive agent, and a solvent, and then drying and rolling the coated negative electrode collector.

[0130] The thickness of the negative electrode collector is generally 3 μm to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity without causing adverse chemical changes in the battery, for example, copper; stainless steel; aluminum; nickel; titanium; fired carbon; copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, etc.; or aluminum-cadmium alloy. In addition, similar to the positive electrode collector, the negative electrode collector may have fine surface irregularities to improve the bonding strength with the negative electrode active material, and the negative electrode collector may be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0131] In one embodiment of the present invention, the negative electrode active material may include a silicon-based material, and may preferably consist of silicon, that is, may be pure Si.

[0132] Silicon materials are selected from Si, SiO xat least one selected from the group consisting of (0 < x < 2) and Si-Y alloys (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Si), preferably Si. Element Y may be selected from the group consisting of: Mg, Ca, Sr, barium (Ba), radium (Ra), Sc, Y, Ti, Zr, hafnium (Hf), (Rf), V, Nb, Ta, (Db), Cr, Mo, W, (Sg), technetium (Tc), rhenium (Re), (Bh), Fe, lead (Pb), ruthenium (Ru), osmium (Os), (Hs), rhodium (Rh), iridium (Ir), palladium (Pd), platinum (Pt), Cu, silver (Ag), gold (Au), Zn, cadmium (Cd), B, Al, Ga, Sn, In, Ge, P, As, antimony (Sb), bismuth (Bi), S, selenium (Se), tellurium (Te), polonium (Po), and combinations thereof. In terms of silicon, its advantage is that the theoretical capacity is higher than that of SiO x .

[0133] Since the capacity of the silicon-based anode active material is nearly 10 times higher than that of graphite, the fast charging performance of the battery can be improved by reducing the mass loading (mg·cm -2 ). However, due to the relatively high loss rate of lithium ions caused by irreversible reactions and the large volume change, there is a problem that may have an adverse effect on the lifespan, and the use of the above non-aqueous electrolyte can solve this problem. Specifically, for the anode containing the silicon-based anode active material, compared with the anode containing only the carbon-based anode active material, there is a problem that the SEI film is prone to rupture and regeneration reactions continuously occur due to the large volume change during the charge and discharge process. Among them, since the SEI film can be strengthened as described above when using the non-aqueous electrolyte of the present invention, this problem can be effectively solved.

[0134] In one embodiment of the present invention, based on the total weight of the anode active material, the content of the silicon-based material may be 5 wt% to 100 wt%, preferably 50 wt% to 100 wt%, more preferably 100 wt%. When the content of the silicon-based material is within the above range, it has the effect of increasing the anode capacity.

[0135] In addition, in addition to the silicon-based material, the anode active material may include at least one selected from the group consisting of: carbon materials capable of reversibly intercalating / deintercalating lithium ions; metals or alloys of lithium and the metal; metal composite oxides; materials that can be doped and undoped with lithium; lithium metal; and transition metal oxides.

[0136] As the carbonaceous negative electrode active material used in a lithium ion secondary battery, carbon materials can be used without particular limitation. As conventional examples, crystalline carbon and / or amorphous carbon can be used. Examples of crystalline carbon can be graphite, such as irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite. Examples of amorphous carbon can be soft carbon (low-temperature sintered carbon), hard carbon, mesophase pitch carbide, and calcined coke.

[0137] As the metal or an alloy of lithium and the metal, a metal selected from the group consisting of Cu, Ni, Na, K, rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of lithium and the metal can be used.

[0138] At least one selected from the group consisting of PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 , Bi 2 O 5 , Li x Fe 2 O 3 (0≤x≤1), Li x WO 2 (0≤x≤1) and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb or Ge; Me': Al, B, P, Si, elements of Groups I, II and III of the periodic table or a halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) can be used as the metal composite oxide.

[0139] The material that can be doped and de-doped with lithium can include Sn, SnO 2and Sn-Y' (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Sn). Element Y' may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Si, In, Ge, P, As, Sb, Bi, S, Se, Te, Po and combinations thereof.

[0140] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt % based on the total weight of the solid matter in the negative electrode slurry.

[0141] The binder is a component that helps the bonding between the conductive agent, the active material and the current collector, wherein the binder is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solids in the negative electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0142] The conductive agent is a component for further improving the conductivity of the negative electrode active material, wherein the conductive agent can be added in an amount of 0.5 wt % to 20 wt % based on the total weight of the solids in the negative electrode slurry. Any conductive agent can be used without particular limitation, as long as the conductive agent has conductivity and does not cause adverse chemical changes in the battery, for example, it can be selected from conductive materials, such as: carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; graphite powder, such as natural graphite, artificial graphite, carbon nanotubes or graphite; conductive fibers, such as carbon fibers or metal fibers; conductive powders, such as fluorocarbon powders, aluminum powders or nickel powders; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0143] The solvent of the negative electrode slurry may include water or an organic solvent such as NMP and alcohol, and may be used in an amount such that a desired viscosity is obtained when the negative electrode active material, the binder and the conductive agent are contained. For example, the content of the solvent may be such that the concentration of the solids in the slurry containing the negative electrode active material, the binder and the conductive agent is 30 wt % to 80 wt %, preferably 40 wt % to 70 wt %.

[0144] (3) Diaphragm

[0145] The lithium secondary battery of the present invention includes a separator between a positive electrode and a negative electrode.

[0146] The separator separates the negative electrode and the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as the separator without particular limitation as long as it is commonly used as a separator in lithium secondary batteries, specifically, a separator having high moisture retention ability for the electrolyte and excellent safety and low ion transport resistance to the electrolyte can be used.

[0147] Specifically, a porous polymer film can be used, for example, a porous polymer film prepared from a polyolefin polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer); or a laminated structure of two or more layers thereof. In addition, a conventional porous nonwoven fabric can be used, for example, a nonwoven fabric formed of high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated diaphragm containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm having a single-layer or multilayer structure can also be used.

[0148] As described above, the lithium secondary battery of the present invention can be suitably used in portable devices such as mobile phones, notebook computers, and digital cameras; and electric vehicles such as hybrid electric vehicles (HEVs).

[0149] Therefore, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module are provided.

[0150] The battery module or battery pack can be used as a power source for at least one of the following large and medium-sized devices: power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs) and plug-in hybrid electric vehicles (PHEVs); or energy storage systems.

[0151] The shape of the lithium secondary battery of the present invention is not particularly limited, and a cylindrical type using a can, a prismatic type, a pouch type, or a coin type can be used.

[0152] The lithium secondary battery of the present invention can be used not only as a battery cell used as a power source for small-sized devices but also as a unit cell in a large or medium-sized battery module including a plurality of battery cells.

[0153] Hereinafter, the present invention will be described in detail according to specific embodiments.

[0154] <Example: Preparation of non-aqueous electrolyte>

[0155] Example 1.

[0156] LiPF was dissolved in ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 30:70. 6 LiPF 6 The non-aqueous organic solution was prepared with a concentration of 1.2 M. A 100 wt % non-aqueous electrolyte was prepared by mixing 0.2 wt % of the compound represented by Chemical Formula 1A, 2 wt % of vinylene carbonate (VC), 5 wt % of fluoroethylene carbonate (FEC), and the remainder of the non-aqueous organic solution.

[0157] Example 2.

[0158] A lithium secondary battery was prepared in the same manner as in Example 1, except that the amount of the compound represented by Chemical Formula 1A was changed to 1.0 wt % during the preparation of the non-aqueous electrolyte.

[0159] Example 3.

[0160] A lithium secondary battery was prepared in the same manner as in Example 1, except that the amount of the compound represented by Chemical Formula 1A was changed to 5.0 wt % during the preparation of the non-aqueous electrolyte.

[0161] Example 4.

[0162] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Chemical Formula 1B was used instead of the compound represented by Chemical Formula 1A in the preparation of the non-aqueous electrolyte.

[0163] Example 5.

[0164] A lithium secondary battery was prepared in the same manner as in Example 4, except that the amount of the compound represented by Chemical Formula 1B was changed to 1.0 wt % during the preparation of the non-aqueous electrolyte.

[0165] Example 6.

[0166] A lithium secondary battery was prepared in the same manner as in Example 4, except that the amount of the compound represented by Chemical Formula 1B was changed to 5.0 wt % during the preparation of the non-aqueous electrolyte.

[0167] Example 7.

[0168] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Chemical Formula 1C was used instead of the compound represented by Chemical Formula 1A in the preparation of the non-aqueous electrolyte.

[0169] Example 8.

[0170] A lithium secondary battery was prepared in the same manner as in Example 7, except that the amount of the compound represented by Chemical Formula 1C was changed to 1.0 wt % during the preparation of the non-aqueous electrolyte.

[0171] Example 9.

[0172] A lithium secondary battery was prepared in the same manner as in Example 7, except that the amount of the compound represented by Chemical Formula 1C was changed to 5.0 wt % during the preparation of the non-aqueous electrolyte.

[0173] Example 10.

[0174] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Chemical Formula 1D was used instead of the compound represented by Chemical Formula 1A in the preparation of the non-aqueous electrolyte.

[0175] Example 11.

[0176] A lithium secondary battery was prepared in the same manner as in Example 10, except that the amount of the compound represented by Chemical Formula 1D was changed to 1.0 wt % during the preparation of the non-aqueous electrolyte.

[0177] Example 12.

[0178] A lithium secondary battery was prepared in the same manner as in Example 10, except that the amount of the compound represented by Chemical Formula 1D was changed to 5.0 wt % during the preparation of the non-aqueous electrolyte.

[0179] Comparative Example 1.

[0180] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Chemical Formula 1A was not added during the preparation of the non-aqueous electrolyte.

[0181] Comparative Example 2.

[0182] A lithium secondary battery was prepared in the same manner as in Example 1, except that a compound represented by the following Chemical Formula Z1 was used instead of the compound represented by Chemical Formula 1A in the preparation of the nonaqueous electrolyte.

[0183] [Chemical formula Z1]

[0184]

[0185] Comparative Example 3.

[0186] A lithium secondary battery was prepared in the same manner as in Comparative Example 2, except that the amount of the compound represented by Chemical Formula Z1 was changed to 1.0 wt % during the preparation of the non-aqueous electrolyte.

[0187] Comparative Example 4.

[0188] A lithium secondary battery was prepared in the same manner as in Comparative Example 2, except that the amount of the compound represented by Chemical Formula Z1 was changed to 5.0 wt % in the preparation of the non-aqueous electrolyte.

[0189] Comparative Example 5.

[0190] A lithium secondary battery was prepared in the same manner as in Example 1, except that a compound represented by the following Chemical Formula Z2 was used instead of the compound represented by Chemical Formula 1A in the preparation of the nonaqueous electrolyte.

[0191] [Chemical formula Z2]

[0192]

[0193] Comparative Example 6.

[0194] A lithium secondary battery was prepared in the same manner as in Comparative Example 5, except that the amount of the compound represented by Chemical Formula Z2 was changed to 1.0 wt % in the preparation of the non-aqueous electrolyte.

[0195] Comparative Example 7.

[0196] A lithium secondary battery was prepared in the same manner as in Comparative Example 5, except that the amount of the compound represented by Chemical Formula Z2 was changed to 5.0 wt % in the preparation of the non-aqueous electrolyte.

[0197] Comparative Example 8.

[0198] A lithium secondary battery was prepared in the same manner as in Example 1, except that a compound represented by the following Chemical Formula Z3 was used instead of the compound represented by Chemical Formula 1A in the preparation of the nonaqueous electrolyte.

[0199] [Chemical formula Z3]

[0200]

[0201] Comparative Example 9.

[0202] A lithium secondary battery was prepared in the same manner as in Comparative Example 8, except that the amount of the compound represented by Chemical Formula Z3 was changed to 1.0 wt % in the preparation of the non-aqueous electrolyte.

[0203] Comparative Example 10.

[0204] A lithium secondary battery was prepared in the same manner as in Comparative Example 8, except that the amount of the compound represented by Chemical Formula Z3 was changed to 5.0 wt % in the preparation of the non-aqueous electrolyte.

[0205] <Experimental Example 1: Performance Evaluation of a Battery Containing a Negative Electrode Material of 100% Silicon>

[0206] Experimental Example 1-0. Preparation of lithium secondary battery

[0207] As the positive electrode active material, Li(Ni 0.8 Co 0.1 Mn 0.1 ) 2 , a conductive agent (carbon black) and a binder (polyvinylidene fluoride) were added to N-methyl-2-pyrrolidone (NMP) at a weight ratio of 97.5:1:1.5 to prepare a positive electrode slurry (solid content: 60 wt%). A 15 μm thick aluminum (Al) film as a positive electrode current collector was coated with the positive electrode slurry, dried and then rolled to prepare a positive electrode.

[0208] 100% Si as a negative electrode active material, SBR-CMC as a binder, and carbon black as a conductive agent were added to water as a solvent at a weight ratio of 95:3.5:1.5 to prepare a negative electrode slurry (solid content: 60 wt %). A 6 μm thick copper (Cu) film as a negative electrode current collector was coated with the negative electrode slurry, dried, and then rolled to prepare a negative electrode.

[0209] By sequentially stacking the positive electrode, coated with inorganic particles (Al 2 O 3 )'s polyolefin porous separator and negative electrode to prepare an electrode assembly.

[0210] The prepared electrode assembly was housed in a pouch-type case, and then the various nonaqueous electrolytes prepared in Examples 1 to 12 and Comparative Examples 1 to 10 were injected therein to prepare a lithium secondary battery.

[0211] Experimental Example 1-1. Capacity and resistance measurement after high temperature storage

[0212] After each lithium secondary battery prepared in Experimental Example 1-0 was subjected to a formation process, the lithium secondary battery was charged at 25°C at a constant current / constant voltage (CC / CV) rate of 0.33C (0.025C cutoff) to 4.3V, and then discharged at a constant current (CC) rate of 0.33C to 2.50V, and then the initial discharge capacity and initial resistance were measured.

[0213] Then, each battery was fully charged to 100% state of charge (SOC) under the same conditions and stored at high temperature (60°C) for 12 weeks. Then, each battery was transferred to a charger and discharger at room temperature (25°C), and the capacity and resistance were measured again. The capacity retention rate and resistance increase rate were calculated by the following mathematical formula 1 and mathematical formula 2, and the results are shown in Table 1.

[0214] Mathematical formula 1: Capacity retention rate (%) = (discharge capacity after high temperature storage / initial discharge capacity) × 100

[0215] Mathematical formula 2: Resistance increase rate (%) = {(resistance after high temperature storage - initial resistance) / initial resistance} × 100

[0216] Experimental Example 1-2. Measurement of gas generation after high-temperature storage

[0217] After the formation process of each lithium secondary battery prepared in Experimental Example 1-0, the lithium secondary battery was charged at a rate of 0.33C (0.025C cut-off) to 4.3V under constant current / constant voltage conditions at 25°C, so that the lithium secondary battery was fully charged to 100% SOC. After the fully charged battery was stored at 60°C for 12 weeks and then transferred to a charger and discharger at room temperature (25°C), the gas collected in the bag was analyzed using a gas chromatography-thermal conductivity detector (GC-TCD), and the relative gas generation of each battery was calculated when the gas generation measured in the battery containing the non-aqueous electrolyte of Comparative Example 1 was set to 100%, as shown in Table 1 below.

[0218] Experimental Example 1-3. High temperature life evaluation

[0219] After the formation process of each lithium secondary battery prepared in Experimental Example 1-0, the lithium secondary battery was charged at 45°C with a constant current / constant voltage (CC / CV) rate of 0.33C (0.025C cutoff) to 4.3V, and then discharged at a constant current (CC) rate of 0.33C to 2.5V.

[0220] One charge / discharge was defined as one cycle, and after the same charge / discharge was repeated 300 times, the capacity retention rate and the resistance increase rate (DCIR increase) were measured by the following Mathematical Formula 3. The measurement results are shown in Table 1 below.

[0221] Mathematical formula 3: Capacity retention rate (%) = (discharge capacity after 300 cycles / discharge capacity after 1 cycle) × 100

[0222] Mathematical formula 4: Resistance increase rate (%) = {(resistance after 300 cycles - resistance after 1 cycle) / resistance after 1 cycle} × 100

[0223] [Table 1]

[0224]

[0225] According to the results of Table 1, it can be confirmed that the batteries using the electrolyte containing the compound of Chemical Formula 1 of Examples 1 to 12 showed better results in all evaluation items such as capacity and resistance characteristics after high-temperature storage, gas generation, capacity and resistance characteristics after high-temperature cycle, etc., compared with the batteries using the electrolyte containing the compound of Chemical Formula 1 of Comparative Examples 1 to 10.

[0226] In particular, when the compound of Formula 1A containing a propargyl group at the R1 position was introduced as shown in Examples 1 to 3, the best results were obtained.

[0227] That is, compared with the batteries of Examples 1 to 12, Comparative Examples 2 to 4 using unsubstituted benzodioxane instead of the compound of Chemical Formula 1, Comparative Examples 5 to 7 using fluorine-substituted benzodioxane, and Comparative Examples 6 to 7 using a benzodioxane having an acetyl group (COCH 3 ) in Comparative Examples 8 to 10, and the poor evaluation results of the battery of Comparative Example 1 in which the compound represented by Chemical Formula 1 is not added, confirm that the gas generation that may occur due to electrochemical decomposition and the resulting degradation of battery performance can be suppressed by introducing a substituent.

[0228] <Experimental Example 2: Performance Evaluation of Batteries Containing Graphite + Si Negative Electrode Materials>

[0229] Experimental Example 2-0. Preparation of lithium secondary battery

[0230] An electrode assembly was prepared in the same manner as in Experimental Example 1-0, except that a negative electrode active material mixed with 97.5 wt % of natural graphite and 2.5 wt % of Si was used instead of a negative electrode active material of 100% Si in the preparation of the negative electrode.

[0231] The prepared electrode assembly was housed in a pouch-type case, and the various nonaqueous electrolytes prepared in Examples 1 to 4, 7, and 10 and Comparative Examples 1, 2, 5, and 8 were injected therein to prepare a lithium secondary battery.

[0232] Experimental Example 2-1. Capacity and resistance measurement after high temperature storage

[0233] For each lithium secondary battery prepared in Experimental Example 2-0, the capacity retention rate and the resistance increase rate were obtained by performing the same process as in Experimental Example 1-1, and the results are shown in Table 2 below.

[0234] Experimental Example 2-2. Measurement of gas generation after high-temperature storage

[0235] For each lithium secondary battery prepared in Experimental Example 2-0, the gas generation amount after high-temperature storage was obtained by performing the same process as in Experimental Example 1-2, and the results are shown in Table 2 below.

[0236] Experimental Example 2-3. High temperature life evaluation

[0237] For each lithium secondary battery prepared in Experimental Example 2-0, the high temperature life was measured by performing the same process as in Experimental Example 1-3, and the results are shown in Table 2 below.

[0238] [Table 2]

[0239]

[0240] According to the results of Table 2, it can be confirmed that even when the negative electrode material is changed, the batteries using the electrolyte containing the compound of Chemical Formula 1 of Examples 1 to 4, 7 and 10 show better results in all evaluation items such as capacity and resistance characteristics after high-temperature storage, gas generation, capacity and resistance characteristics after high-temperature cycle, etc., compared with the batteries using the electrolyte containing the compound of Chemical Formula 1 of Comparative Examples 1, 2, 5 and 8.

[0241] <Experimental Example 3: Performance evaluation of batteries containing NCM613 positive electrode material>

[0242] Experimental Example 3-0. Preparation of lithium secondary battery

[0243] In addition to using Li(Ni 0.6 Co 0.1 Mn 0.3 ) 2 The positive electrode active material is replaced by Li(Ni 0.8 Co 0.1 Mn 0.1 ) 2 An electrode assembly was prepared in the same manner as in Experimental Example 1-0, except for the positive electrode active material.

[0244] The prepared electrode assembly was housed in a pouch-type case, and the various nonaqueous electrolytes prepared in Examples 1 to 4, 7, and 10 and Comparative Examples 1, 2, 5, and 8 were injected therein to prepare a lithium secondary battery.

[0245] Experimental Example 3-1. Capacity and resistance measurement after high temperature storage

[0246] For each lithium secondary battery prepared in Experimental Example 3-0, the capacity retention rate and resistance increase rate were obtained by performing the same process as in Experimental Example 1-1, except that the upper limit voltage was changed to 4.4 V instead of 4.3 V. The results are shown in Table 3 below.

[0247] Experimental Example 3-2. Measurement of gas generation after high-temperature storage

[0248] For each lithium secondary battery prepared in Experimental Example 3-0, the same process as in Experimental Example 1-2 was performed except that the upper limit voltage was changed to 4.4 V instead of 4.3 V, and the gas generation after high temperature storage was obtained. The results are shown in Table 3 below.

[0249] Experimental Example 3-3. High temperature life evaluation

[0250] For each lithium secondary battery prepared in Experimental Example 3-0, the high temperature life was measured by performing the same process as in Experimental Example 1-3, except that the upper limit voltage was changed to 4.4 V instead of 4.3 V. The results are shown in Table 3 below.

[0251] [Table 3]

[0252]

[0253] According to the results of Table 3, it can be confirmed that even when the positive electrode material is changed, the batteries using the electrolyte containing the compound of Chemical Formula 1 of Examples 1 to 4, 7 and 10 show better results in all evaluation items such as capacity and resistance characteristics after high-temperature storage, gas generation, capacity and resistance characteristics after high-temperature cycle, etc., compared with the batteries using the electrolyte containing the compound of Chemical Formula 1 of Comparative Examples 1, 2, 5 and 8.

Claims

1. A non-aqueous electrolyte for a lithium secondary battery, comprising: a lithium salt; an organic solvent; and a compound represented by Chemical Formula 1: [Chemical formula 1] in, In Chemical Formula 1, R1 is -COR, -COOR', -NCO, a nitrile group, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms, R2 is: a halogen group; -COR"; -COOR"'; -NCO; a nitrile group; an alkyl group having 1 to 10 carbon atoms which is unsubstituted or substituted with at least one halogen group; an alkenyl group having 2 to 10 carbon atoms; or an alkynyl group having 2 to 10 carbon atoms, R, R', R", and R'" are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms, n is 1 or 2. When n is 2, two R1s are the same as or different from each other, and m is any integer from 0 to 8-n.

2. The non-aqueous electrolyte for lithium secondary battery according to claim 1, wherein R1 is -COR, -COOR', -NCO or a nitrile group.

3. The non-aqueous electrolyte for lithium secondary battery according to claim 1, wherein R and R' are each independently an alkyl group having 1 to 10 carbon atoms or an alkynyl group having 2 to 10 carbon atoms.

4. The non-aqueous electrolyte for lithium secondary battery according to claim 1, wherein The compound represented by Chemical Formula 1 is represented by Chemical Formula 1-1: [Chemical formula 1-1] Among them, in chemical formula 1-1, R1 and R2 are as defined in Formula 1, and k is an integer from 0 to 4.

5. The non-aqueous electrolyte for lithium secondary battery according to claim 1, wherein The compound represented by Chemical Formula 1 may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the non-aqueous electrolyte.

6. The non-aqueous electrolyte for lithium secondary battery according to claim 1, wherein The compound represented by Chemical Formula 1 may be included in an amount of 0.15 wt % to 3 wt % based on the total weight of the non-aqueous electrolyte.

7. The non-aqueous electrolyte for a lithium secondary battery according to claim 1, further comprising at least one additive selected from the group consisting of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, succinonitrile, 1,3,6-hexanetrinitrile, lithium difluorooxalatoborate, lithium tetrafluoroborate, 1,3-propane sultone, prop-1-ene-1,3-sultone, ethylene sulfate and lithium difluorophosphate.

8. The non-aqueous electrolyte for lithium secondary battery according to claim 1, wherein The organic solvent includes a mixture of at least two selected from the group consisting of a cyclic carbonate-based solvent, a linear carbonate-based solvent, and a linear ester-based solvent.

9. A lithium secondary battery comprising: a positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; A separator disposed between the positive electrode and the negative electrode; and The non-aqueous electrolyte according to claim 1.

10. The lithium secondary battery according to claim 9, wherein: The positive electrode active material includes a lithium composite transition metal oxide represented by Chemical Formula 2: [Chemical formula 2] Li 1+x (Ni a Co b Mr c M d )O2 Wherein, in Chemical Formula 2, M is at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and 1+x, a, b, c and d are the atomic fractions of the individual elements, Among them, -0.2≤x≤0.2, 0.6≤a<1, 0 <b≤0.3,0<c≤0.3,0≤d≤0.1,a+b+c+d=1。 11. The lithium secondary battery according to claim 10, wherein: a, b, c and d in chemical formula 2 satisfy 0.70≤a<1, 0 <b≤0.2,0<c≤0.2,0≤d≤0.1。 12. The lithium secondary battery according to claim 9, wherein: The negative electrode active material includes a silicon-based material.

13. The lithium secondary battery according to claim 12, wherein: The negative electrode active material is composed of silicon.

Citation Information

Patent Citations

  • Auto-removal counter-stacker

    KR1020220085817A

  • Integrated piping system for heating and hot water

    KR1020230087775A